Effect on Composition of Planting Media with Biological Agents to Improve Physical and Chemical Properties of the Soil - Kharisun; Fadillah; Mujiono; Suciati (Current Research Progress in Agricultural Sciences Vol. 9, 2025)
The use of planting media using a combination of soil, inorganic and organic natural ameliorant materials, and biological agents may provide better physical and chemical properties of planting media in order to get maximum production of plants. The composition of soil, manure and husk charcoal can support the growth and development of plants. This research aims to study the effect of various compositions of soil organic matter, zeolite, husk charcoal and biological agents on physical and soil chemical properties of planting media. This research was done in a pot experiment in a greenhouse. The experiment was designed as a randomized complete block design (RCBD) factorial. The first factor was the type of biological agent consisting of control or without, PGPR and Trichoderma sp. The second factor was a composition of media with a combination of 50% soil and 50% soil enhancers consisting of goat manure, zeolite and husk charcoal with a combination of 11 combinations. In total, there were 33 treatment combinations with 3 replications each. Results showed that the composition of soil media had an influence on water retention, bulk density, porosity, pH, DHL, C/N ratio, N-total, N-available, P2O5, K2O, and C-organic. The results of analysis showed that the composition of soil conditioner and biological agents significantly affected electrical conductivity. Planting media with the proportion of goat manure, zeolite and husk charcoal at 3: 1: 2 gives the best result when compared to other planting media. It was represented by the highest value of 5.81% C-organic and 0.69% N total. As biological agents, PGPR gives better influence on electrical conductivity at value 291.58 \(\sqcap\)S cm-3. In conclusion, the combination of goat manure, zeolite, and husk charcoal in the right proportions can significantly improve soil quality, as well as benefit plant growth by enhancing nutrient content, soil structure, and conductivity.